2017
DOI: 10.9734/arrb/2017/34211
|View full text |Cite
|
Sign up to set email alerts
|

Ecology and Protein Composition of Polypedates leucomystax (Gravenhorst, 1829) (Anura: Rhacophoridae) Foam Nests from Peninsular Malaysia

Abstract: The four-lined tree frog, Polypedates leucomystax, spawns its eggs in a moist structure called a foam nest. Four foam nests constructed by this species were collected from the Sungai Sedim Recreational Forest, Kedah, Peninsular Malaysia. Two foam nests were found deposited on the leaves of low vegetation hanging over a rock pool. One was attached inside a water tank, and one was found on grass near an ephemeral puddle. In the laboratory, the foam nests were freeze-dried and the protein concentrations quantifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
(26 reference statements)
0
8
0
1
Order By: Relevance
“…Malaysian (Sarawak) frog species' skin secretions showed that some of the frog species contain AMPs and some are more potent than others (Sabri et al, 2018;Shahabuddin et al, 2018). Brevinin-2 has been identified from protein profiling of a foam nest from Polypedates leucomystax (Shahrudin et al, 2017) At least five studies have been performed on extralimital frog species that can also be found in Malaysia, Table 2, (Lu et al, 2008;Song et al, 2009;Al-Ghaferi et al, 2010;Wang et al, 2012;Suhyana et al, 2015). Skin secretions of Limnonectes kuhlii, Kuhl's wart frog, from China revealed that the five novel AMPs that were purified and characterised showed strong antimicrobial effects Gram-positive and Gram-negative bacteria and fungi (Wang et al, 2012a).…”
Section: Studies Of Amp S In Malaysian Amphibian Speciesmentioning
confidence: 99%
See 4 more Smart Citations
“…Malaysian (Sarawak) frog species' skin secretions showed that some of the frog species contain AMPs and some are more potent than others (Sabri et al, 2018;Shahabuddin et al, 2018). Brevinin-2 has been identified from protein profiling of a foam nest from Polypedates leucomystax (Shahrudin et al, 2017) At least five studies have been performed on extralimital frog species that can also be found in Malaysia, Table 2, (Lu et al, 2008;Song et al, 2009;Al-Ghaferi et al, 2010;Wang et al, 2012;Suhyana et al, 2015). Skin secretions of Limnonectes kuhlii, Kuhl's wart frog, from China revealed that the five novel AMPs that were purified and characterised showed strong antimicrobial effects Gram-positive and Gram-negative bacteria and fungi (Wang et al, 2012a).…”
Section: Studies Of Amp S In Malaysian Amphibian Speciesmentioning
confidence: 99%
“…Amphibians produce skin secretions when they feel threatened/stressed due to their host defence mechanism (Hancock and Sahl, 2006). Zahri et al (2015) and Shahrudin et al (2017) directly collected secretions without stimulation because parotoid secretions and foam nests do not need any stimulant for collection. These secretions were collected either by immersing the animals in a low concentration, salt solution (sodium chloride or sodium acetate) or directly rinsing the animals with deionised water.…”
Section: Different Approaches To Discover the Amps In Malaysian Amphimentioning
confidence: 99%
See 3 more Smart Citations